An Analysis of Students’ Ability In Using Subject-Verb Agreement - Kurniawan, Iwan; Seprizanna, Seprizanna (English Education: Jurnal Tadris Bahasa Inggris, 2016)
The objective of this research was to describe the ability of students in using subject-verb agreements of three tenses, namely: Present Tense, Past Tense and Present Perfect Tense.The result of the data analysis of students’ ability in using subject-verb agreement of the eighth grade students of SMP Islamiyah Kotaagung. It was found that the students’ ability in using subject-verb agreement of the eighth grade students of SMP Islamiyah Kotaagung in the academic year of 2016/2017 had fair level by mean score 58.03.